Animal Abuse Helping Animals and People - Tiplady, Catherine (CABI, 2014)
Catherine Tiplady has been involved in research on animal abuse for several years and as a veterinarian has also first-hand experience of abuse cases. She initially studied the role of pets in domestic violence situations in her Veterinary Honours programme, and she continued this theme in her postgraduate degree. Under the guidance of supervisor Deborah Walsh, a specialist in domes- tic violence, and myself, Catherine has developed a keen understanding of this topic in a short space of time. In her initial studies she demonstrated the particular vulnerability of dogs in domestic violence situations, but it is clear that all animals are at risk of both verbal and physical abuse. In this book she brings together several years of research on animal abuse, as well as including contributions from key workers in this field, such as Allie Phillips, the celebrated lawyer who special- ises in cases involving animal abuse, David Bailey, forensic veterinarian, Howard Ralph, wildlife vet- erinarian and volunteers from aid agencies. Case studies provide the detail to keep the reader closely in touch with the real world, and interviews with key people provide an intensely personal experi- ence of abuse. Phil Arkow describes how veterinarians can make a difference by having a critical eye to detect and report animal abuse, giving them a central role and responsibility in managing abuse cases. The vital function that animal cruelty organizations fulfil is recognized; with their protective role and that of veterinarians it may be unclear to readers how widespread abuse is allowed to hap- pen. The fallibility of human nature and inadequate resources are regrettably too often the reason. With many terms in this area being emotive, Catherine has used her scientific background to first define and then confine her discussions to her clear understanding of these terms. Abuse is described in relation to the uses of animals by humans that are most commonly found in the Western world. This is entirely logical because as the many instances of abuse in provision of food and fibre for humans are presented, it becomes only too clear that humans are selfish individuals, tolerating cruelty far more readily when we have something to gain from it. These are widespread instances of abuse, but Catherine also successfully charts many less common forms of abuse, from bear baiting to bestiality. Pet abuse is a field that receives little publicity, unlike farm animal abuse, yet it is apparent from Catherine’s major focus on this topic that may be very common. Pet ownership is more popular than ever, yet the pressures of modern living can reduce the animals’ welfare, with busy working hours for both partners, high-density living and many possibilities for alternative uses of leisure time. However, pets’ important role in many households inevitably brings them into close proximity with domestic violence, rendering them vulnerable to abuse.